ANALISIS PELUANG TINGKAT COLLECTABILITY KREDIT MODAL KERJA: STUDI KASUS PADA BANK KREDIT KELURAHAN KETAPANG, KEC. KADEMANGAN, PROBOLINGGO - Dimaz Bagus Aditya Nugraha (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The purpose of this research is investigated and examined the influence of rate of interest, job, and state of the job and time of credit toward amount of credit at BKK Ketapang Kecamatan Kademangan Probolinggo. The Hypotesis that formulated in this research is there is influence rate of interest, job, state of the job and time of credit toward amount of credit at BKK Ketapang Kecamatan Kademangan Probolinggo. This research is empirical survey at BKK Ketapang Kecamatan Kademangan Probolinggo. Data that used in this research is secondary and primery data. Data have been collected from BKK Ketapang Kecamatan Kademangan Probolinggo in 2012. The data have been colleted in this research as 100 respondents. The analisys that used is logistic regression. The result of logistic regression show that rate of interest, job, state of the job and time of credit have significant influence toward amount of credit at BKK Ketapang Kecamatan Kademangan Probolinggo as simultance. Kata Kunci: rate of interest, job, state of the job, time of credit, amount of credit